Mapping the role of ‘transnational family habitus’ in the lives of young people and children - Zontini, Elisabetta; Reynolds, Tracey (Wiley, 2017)
In this article, we develop the concept of ‘transnational family habitus’ as a theoretical tool for making sense of the ways in which children and young people from a migrant background are ‘doing families’ transnationally. Drawing on over a decade of cumulative research on Caribbean and Italian families in the UK, as well as on a new joint research project, we first investigate the opportunities and consequences of a transnational family habitus on family arrangements, kinship relationships and identity within a transnational context. Second, we analyse the role of these young people's structural location in Britain in shaping the boundaries of their transnational family habitus. We argue that one should see a transnational family habitus as an asset that can potentially disrupt conventional understandings of belonging and processes of inclusion and exclusion. However, we also detail how social divisions of class, race, and increasingly migration status, shape such a habitus.